Behaviour of Non-Linear Partially Saturated Soils below Strip Footings - A. Waryosh, Waleed; K. AbdulRahman, Shaymaa; M. Khather, Ali (Journal of Engineering and Sustainable Development, 2008)
The effect of time dependent compression of consolidation settlement is modeled by using the finite element formulation of the coupled field equations for deformation and excess pore water pressure generated by an increment of loading applied to a saturated soil is studied. This formulation is extended based on Biot’s theory to include the partially saturated soil; the formulation has been developed by noting that air and water pressure in partially saturated soils are approximately equal at high degrees of saturation. This led to a relatively simple formulation which can have a range of practical applications.The result shows that there is an influence of partial soil saturation on strip footings behaviour. Both partially saturated and conventional saturated finite element analyses are performed with the Modified Cam Clay Model presented in this study.